Caracterização e secagem da madeira de 12 espécies amazônicas - Susin, Felipe (2018)
Drying wood is a fundamental step to adding quality to it, aiming the manufacture of durable products. The existing relation between some specific characteristics of wood and its behaviour during the drying process requires that studies be carried with the purpose to understand and consolidate such relations and how they influence drying. Therefore, the objective of this study was to group similar species based on preliminary essays on drying, as a result of the behaviour of the wood for the species Euxylophora paraensis, Ocotea aciphylla, Astronium lecointei, Couratari guianensis, Couratari stellata, Hymenolobium petraeum, Goupia glabra, Vochysia guianensis, Qualea paraensis, Trattinnickia burserifolia, Apuleia leiocarpa e Dipteryx odorata. Physical-chemical properties, as well as the behaviour of wood were evaluated under drying process at 60º. Reduced-size samples were used in this procedure. The densisty of the species used showed variation from 0,41 g.cm-3 for Trattinnickia burserifolia until 0,92 g.cm-3 for Dipteryx odorata, while the average lowest values of retractability were checked for the wood Couratari guianensis. The species showed significant differences in the drying rates. Wood such as Ocotea aciphylla and Goupia glabra revealed low values, when compared to that those low-speed-drying species and the last species with propensity for defects. The species of wood showing the fastest drying process, such as Apuleia leiocarpa and Qualea paraensis attested tendency to defects such as warps and top cracks. A group 83% similar was formed with the woods Hymenolobium petraeum, Ocotea aciphylla and Dipteryx odorata. For this group a drying program that allows the species to dry continuously was created, showing that the group analysis enabled the grouping of highly similar species, in what concerns to their behavior under the drying process.